Advanced Oxidation Processes at Laboratory Scale: Environmental and Economic Impacts - Giménez, Jaime; Bayarri, Bernardí; González, Óscar; Malato, Sixto; Peral, José; Esplugas, Santiago (ACS sustainable chemistry & engineering, 2015)
Advanced Oxidation Processes (AOPs) are widely used at laboratory scale in the treatment of different pollutants, and many references appear in the literature on this subject. However, there are not many works devoted to the study of the impact of these laboratory works from an environmental and economic point of view. For these reasons, this study is focused on the environmental impact evaluation, by LCA, of two AOPs (photocatalysis and pho-Fenton) in two different experimental setups (solarbox and CPCs), for the treatment of metoprolol. LCA has proved to be useful to compare the AOPs and the tested devices. In the same way, an economic assessment was made for the same AOPs and installations. Conclusions are very meaningful, pointing out that the cost of such experiments at laboratory level is not negligible and has to be seriously considered. As a consequence, laboratory work has to be accurately planned, and analysis techniques and proofs to be used must be carefully selected to avoid excessive increases in the costs of laboratory experiments.